ANALISIS HABITS OF THINKING INTERDEPENDENTLY (HTI) SISWA SMP DALAM PEMBELAJARAN KOOPERATIF - Ummul Huda (Ta'dib, 2016)
AbstractThis research is motivated by the lack of social interaction among students to improve the quality of understanding and learning. Yet this is very important  to achieve maximum results in learning, including the habit of students to give feedback, criticism, responses, compliments to each other; mutual energies and thoughts to the group; more concerned with common interests rather than personal interests; mutual aid among fellow members of the group to ensure that all members understand the task they are doing; and they not only contribute but also learn something from the group. Therefore, this study discusses about how the image of students HTI in learning math is done cooperatively. The method used is descriptive quantitative research, the subjects are students of SMPN 5 Bandung totaling 29 person. The instrument that this research used was a questionnaire and observation sheet. The result of this research show that students’ HTI in learning cooperative are good, such as they are care/emphathize to the others feeling and thought, to look at and listen to others with understanding and empathy, showing their independence in learning and collaborative team.Kata Kunci: Habit of Thinking Interdependently (HTI), Pembelajaran Kooperatif